Vertical Fiscal Balance and Local Fiscal Discipline in Indonesia - Deni Sarjoko; Moh. Khusaini; Rachmad Kresna Sakti (Journal of International Conference Proceedings (JICP), 2022)
Fiscal discipline is the key value to manage public finance. In term of local government, maintaining fiscal discipline can improve basic services and public confidence provision. The research purpose is to give an input for the government to determine regional expansion policy. The analysis applies fixed effect model to analyze the relationship between vertical fiscal balance and local fiscal discipline in 491 districts/cities in Indonesia for 2010 to 2020. This study found the indication that the lower vertical fiscal balance, the lower the fiscal discipline of the district/city governments to collect local taxes, so regional development highly depends on intergovernmental transfer. The results indicate that the increase of vertical fiscal balance will increase local fiscal discipline. In addition to be driven by a vertical fiscal balance, local fiscal discipline increase is also driven by population density increase, the tertiary sector share, and Gross Regional Domestic Product per capita. It is important for the governments to consider vertical fiscal balance, population density, the share of the tertiary sector, and GRDP per capita, as variables to approve proposed regional expansion so that each regional expansion results in optimal public services.Keywords: Vertical Fiscal Imbalance, Local Own-Source Revenue, Population Density, Tertiary Sector Share, Gross Domestic Regional Product.